2010
DOI: 10.1088/0004-637x/717/2/1022
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Spectral Modeling of the Hard X-Ray Emission of Gx 339–4 in a Bright Low/Hard State

Abstract: We study the high-energy emission of the Galactic black hole candidate GX 339−4 using INTEGRAL/SPI and simultaneous RXTE/PCA data. By the end of 2007 January, when it reached its peak luminosity in hard X-rays, the source was in a bright hard state. The SPectrometer on INTEGRAL (SPI) data from this period show a good signal-to-noise ratio, allowing a detailed study of the spectral energy distribution up to several hundred keV. As a main result, we report on the detection of a variable hard spectral feature ( 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 57 publications
4
42
0
Order By: Relevance
“…In addition a high energy excess above the cut-off energy is detected in the brightest sources 3,4,5,6 (see Fig. 1).…”
Section: High Energy Emission Of Black Hole Binariesmentioning
confidence: 87%
“…In addition a high energy excess above the cut-off energy is detected in the brightest sources 3,4,5,6 (see Fig. 1).…”
Section: High Energy Emission Of Black Hole Binariesmentioning
confidence: 87%
“…Observational evidence of the presence of non-thermal particles in accretion flows includes detection of MeV tails (e.g., Droulans et al 2010;Zdziarski et al 2012) and patterns of optical/infrared evolution , both observed in stellar black-hole systems. However, these features are produced by nonthermal electrons, which may come from pion decay, and in principle, they do not require direct acceleration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the problem must be treated numerically Malzac & Belmont 2009;Veledina et al 2013). A comparison of modeled spectra obtained from self-consistent electron distributions against the observed spectra has been performed for the BH binaries Cyg X-1 and GX 339-4 in the X-ray/γ-ray regime Malzac & Belmont 2009;Droulans et al 2010;Del Santo et al 2013). However, simultaneous comparison with the optical/UV data has not been presented to date.…”
Section: Self-consistent Physical Modelingmentioning
confidence: 99%